Freak Fights. On the Appeal of Blurring - Nosal, Przemysław; Kępińska, Adrianna; Łatwis, Karolina; Najdul, Wiktoria; Pękal, Barbara (Studia Socjologiczne, 2026)
Freak fights are fights staged in the ring by celebrities who are sports amateurs. They enjoy great popularity among the public, generate significant profits, and produce a lot of cultural content. However, they are also criticised for promoting violence and hate speech, and for showing a lack of respect for fair play. Their presence in the public sphere has sparked an important discussion about the fundamental principles of society. This article aims to explore the reasons behind the popularity of freak fights based on qualitative research conducted with young people who watch them. Four main reasons for following these events were identified based on the results obtained: the redefinition of the traditional sporting formula, the decontextualisation of celebrities, the ambivalence of the emotions experienced in connection with them, and the guilty pleasure derived from watching them. More broadly, the popularity of freak fights is linked to the appeal of ‘blurring genres’ – in this case, the genre of sporting events.